2011
DOI: 10.2516/ogst/2011101
|View full text |Cite
|
Sign up to set email alerts
|

A New Multi-Sample EOS Model for the Gas Condensate Phase Behavior Analysis

Abstract: Résumé -Un nouveau modèle d'EOS multi-échantillon pour l'analyse de comportement de phase de condensat de gaz -Les équations d'état (EOS) sont largement utilisées pour prédire le comportement des phases des fluides de réservoir. Par rapport aux modèles classiques de corrélation, la précision des techniques de modélisation par EOS a permis une amélioration des prédictions des propriétés de ces fluides. Lorsque le pétrole brut ou les condensats de gaz ont été correctement caractérisés au moyen d'un nombre limité… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…One of the earliest attempts was introduced by Katz, employing an exponential model as the distribution function. This method was based on the extended analysis of the behaviour of different condensate systems . Another splitting scheme, proposed by Pederson et al, was based on assuming a logarithmic relationship between the carbon number of SCN groups and their corresponding mole fractions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest attempts was introduced by Katz, employing an exponential model as the distribution function. This method was based on the extended analysis of the behaviour of different condensate systems . Another splitting scheme, proposed by Pederson et al, was based on assuming a logarithmic relationship between the carbon number of SCN groups and their corresponding mole fractions.…”
Section: Introductionmentioning
confidence: 99%
“…3 The accumulated condensate bank also changes the phase composition, which in turn reshapes the phase diagram and other properties of reservoir fluid. 4 Results from the case study [5][6][7] showed that the impact of condensate banking would be severe for these reservoirs if the physical processes expected in these reservoirs are not correctly modelled.…”
Section: Introductionmentioning
confidence: 99%